2000
DOI: 10.1523/jneurosci.20-09-03387.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Precision of Single Neuron Responses in Cortical Area V1 during Stereoscopic Depth Judgments

Abstract: The performance of single neurons in cortical area V1 of alert macaque monkeys was compared against the animals' psychophysical performance during a binocular disparity discrimination task. Performance was assessed with stimuli that consisted of a patch of dynamic random dots, whose disparity varied from trial to trial, surrounded by an annulus of similar dots at a fixed disparity. On each trial, the animals indicated whether the depth of the central patch was in front of or behind the annulus. For each dispar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 35 publications
10
78
0
Order By: Relevance
“…Although it might be surprising to some readers, this observation is consistent with studies that involve fine discrimination tasks in other sensory systems, where perceptual threshold may be set by the most sensitive neurons available (4). For example, similar findings have been reported for orientation discrimination in primary visual cortex (V1) (31), fine direction discrimination in the middle temporal (MT) visual area (7), and fine binocular disparity discrimination in areas V4 (32) and V1 (33). In contrast, studies that have compared neuronal and psychophysical performance in coarse discrimination or amplitude discrimination tasks have often reported that many single neurons are more sensitive than the animal (5, 6, 9, but also ref.…”
Section: Discussionsupporting
confidence: 74%
“…Although it might be surprising to some readers, this observation is consistent with studies that involve fine discrimination tasks in other sensory systems, where perceptual threshold may be set by the most sensitive neurons available (4). For example, similar findings have been reported for orientation discrimination in primary visual cortex (V1) (31), fine direction discrimination in the middle temporal (MT) visual area (7), and fine binocular disparity discrimination in areas V4 (32) and V1 (33). In contrast, studies that have compared neuronal and psychophysical performance in coarse discrimination or amplitude discrimination tasks have often reported that many single neurons are more sensitive than the animal (5, 6, 9, but also ref.…”
Section: Discussionsupporting
confidence: 74%
“…Before training for the task of the present study, both monkeys had been fully trained on a stereoacuity task, similar to that described previously (Prince et al, 2000), and had been psychophysical subjects in a study of stereoacuity as a function of interocular delay (Read and Cumming, 2005). The monkeys viewed the RDS stimulus while fixating on a 0.2 ϫ 0.2°fixation square.…”
Section: Methodsmentioning
confidence: 99%
“…The first explanation seems improbable: V1 is the likely source of disparity signals for neurons in V2. Furthermore, several limitations in stereoscopic performance (especially spatial and temporal resolution) seem to reflect processing in V1 (Prince et al, 2000;Nienborg et al, 2004Nienborg et al, , 2005. The second explanation would make it quite natural that CPs are not significant in V1: One need only suppose that the top-down signal does not reach all the way back to V1.…”
mentioning
confidence: 99%
“…First, the neuronal modulation that occurs when attention is directed to a stimulus (Spitzer et al, 1988) or when effort is increased (Spitzer and Richmond, 1991) is typically an enhancement, which is consistent with behavioral improvements. Second, a rough correspondence exists between behavioral performance and the ability of individual neurons to discriminate among or detect stimuli (Parker and Hawken, 1985;Barlow et al, 1987;Britten et al, 1992;Geisler and Albrecht, 1997;Prince et al, 2000). Because these studies are likely to have spanned a range of attentional states, it is possible that the relationship between neuronal activity and behavioral performance persists across different attentional conditions.…”
Section: Abstract: Attention; Macaque Monkey; Mt; Vip; Vision; Motionmentioning
confidence: 99%